2021
DOI: 10.3390/ijms222212446
|View full text |Cite
|
Sign up to set email alerts
|

Keratins as an Inflammation Trigger Point in Epidermolysis Bullosa Simplex

Abstract: Epidermolysis bullosa simplex (EBS) is a group of inherited keratinopathies that, in most cases, arise due to mutations in keratins and lead to intraepidermal ruptures. The cellular pathology of most EBS subtypes is associated with the fragility of the intermediate filament network, cytolysis of the basal layer of the epidermis, or attenuation of hemidesmosomal/desmosomal components. Mutations in keratins 5/14 or in other genes that encode associated proteins induce structural disarrangements of different stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 221 publications
(330 reference statements)
0
13
0
Order By: Relevance
“…Specifically, we showed that MSC from umbilical cord contributed to form a stratified organotypic culture but not a typical epithelial structure in both used dermal equivalents—collagen with fibroblasts and the decellularized matrix MatriXpec™, being the structural and chemical characteristics of dermal equivalents critical for the epidermis stratification and keratinocyte complete differentiation. In those organotypic cultures it was verified the expression of essential epidermal molecular markers such as cytokeratins (CK 5 and CK10), involucrin, filaggrin and the epidermal kallikreins (KLK), proteins that are critical to maintaining skin function and homeostasis ( Kalinska et al, 2016 ; Evtushenko et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we showed that MSC from umbilical cord contributed to form a stratified organotypic culture but not a typical epithelial structure in both used dermal equivalents—collagen with fibroblasts and the decellularized matrix MatriXpec™, being the structural and chemical characteristics of dermal equivalents critical for the epidermis stratification and keratinocyte complete differentiation. In those organotypic cultures it was verified the expression of essential epidermal molecular markers such as cytokeratins (CK 5 and CK10), involucrin, filaggrin and the epidermal kallikreins (KLK), proteins that are critical to maintaining skin function and homeostasis ( Kalinska et al, 2016 ; Evtushenko et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, intermediate filaments provide cells and tissues with resistance to mechanical and chemical stresses, particularly in the heart, skin, and liver ( 20, 25, 26 ). Interestingly, ER stress has been implicated in epidermal fragility disorders caused by keratin or desmosome dysfunction ( 27 ). Conversely, loss of function mutations in the ER calcium pump SERCA2 cause desmosome and skin defects in Darier’s disease ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ER stress has been implicated in epidermal fragility disorders caused by keratin or desmosome dysfunction (27). Conversely, loss of function mutations in the ER calcium pump SERCA2 cause desmosome and skin defects in Darier's disease (28) .…”
Section: Keratin Mutants That Cause Epidermal Blistering Alter Er Mem...mentioning
confidence: 99%
“…At the same time, it can upregulate glutamine levels; stimulate protein synthesis; and provide nutritional support for mucosal cells, fibroblasts, and other rapidly proliferating cells ( Cheng and Eriksson, 2017 ). Previous studies have shown that KFX can effectively promote angiogenesis and granular-tissue growth, improve wound microcirculation, accelerate tissue repair and regeneration, eliminate edema, and enhance the immune function, which can help repair and heal ulcers as soon as possible, protect the ulcer surface from infection, and avoid necrosis ( Chigurupati et al, 2013 ; Evtushenko et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%